PENGARUH INOVASI DAN KUALITAS PRODUK TERHADAP LOYALITAS KONSUMEN TEH BOTOL SOSRO DENGAN KEPUASAN SEBAGAI VARIABEL INTERVENING - Sujadi, Tutut Paradhiba; Wahyono, Wahyono (Management Analysis Journal, 2015)
This study aims to investigate the influence of innovation and product quality on customer loyalty Tea Botol Sosro with satisfaction as an intervening variable. The study population was all citizens who live in sekaran both local residents and students UNNES. Sampling by using accidental sampling technique, the sample size is determined by using iteration and obtained a sample of 102 people. Data collection methods used were questionnaires, and the methods of analysis, test instrument (validity and reliability testing). Analysis of data using path analysis (Path Analysis), wherein the variables used include innovation, product quality, satisfaction, and customer loyalty. Conclusions from this research is that there is influence directly or indirectly variable product innovation and product quality on customer loyalty through satisfaction Botol Sosro as an intervening variable. Suggestion for the company is to be always doing research to innovate in developing products Sosro Tea produced, as well as improve the quality of its products.